Avian β-defensins expression for the innate immune system in hen reproductive organs - Y. Yoshimura (2015)
Avian β-defensins (AvBDs) attack various microorganisms and may have efficacy to protect tissues from infection by unforeseen pathogenic microbes. This article describes the mechanism by which AvBDs are expressed in the innate immune system in hen reproductive organs. Both ovary and oviduct express Toll-like receptors (TLRs), which recognize microbe-associated molecular patterns, and express and produce AvBDs mRNA and peptides, which are antimicrobial peptides. The interaction of TLRs with their ligands upregulates the expression of AvBDs and proinflammatory cytokines, and proinflammatory cytokines also induce expression of AvBDs. The synthesized AvBDs are predicted to kill the microbes. However, strategies to enhance innate immune functions have not yet been established. Breeding of birds that have a higher ability to synthesize antimicrobial peptides in response to pathogens may be one such strategy. Because the ovary and oviduct are unique organs regulated by the endocrine system, consideration of the role of gonadotropic and gonadal hormones may also be important for the enhancement of local defense function. Physiological information about the mechanism of pathogen recognition and AvBD synthesis is essential to enhance immunodefense functions in the reproductive organs.